Dinamika Implementasi Kebijakan Penertiban dan Pembinaan Masalah Sosial di Kota Jambi : Sebuah Studi Pemetaan - Chessi Adeliya Simatupang; Dinda Syufradian Putra; Azira Novia Rizal (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2026)
This research is motivated by the complex problems of street children, vagrants, and beggars in Jambi City, which are influenced by poverty, urbanization, and weak social protection. This phenomenon not only impacts public order but also reflects the suboptimal social welfare system at the regional level. Although local governments have implemented various policies through social order and rehabilitation approaches, their effectiveness still faces various structural and cultural challenges. This study uses Bryson's Policy Implementation Mapping theoretical framework, which includes indicators of interests, resources, channels, potential participation, level of influence, implications, and actions as the main analysis. The research approach used is a qualitative case study design to understand the dynamics of policy implementation in depth. Data collection techniques were carried out through in-depth interviews, participant observation, and documentation, with informants selected using purposive sampling until data saturation was achieved. The results show that policy implementation mapping has been carried out through collaboration between the Social Service and the Public Order Agency (Satpol PP) with a structured preventive, repressive, and rehabilitative approach. However, implementation has not been optimal due to limited rehabilitation facilities, lack of coordination between agencies, low community participation, and high mobility of beggars from outside the region. Furthermore, there is a gap between high administrative achievements and the reality on the ground, which still shows a high rate of returning to the streets. This study concludes that mapping policy implementation requires a more holistic, sustainable approach based on economic empowerment and strengthened cross-sectoral coordination to address this social issue more effectively and effectively.